3D graphics visualization for interactive mobile users navigation - Mantoro, Teddy; Abubakar, Adamu; Ayu, Media Anugerah (World Scientific and Engineering Acadddemy and Society (WSEAS), 2012)
3D map visual navigation comes into being as a result of the drawbacks in two-dimensional map exhibit navigation approaches, which are the most commonly available. The information provided for user in 2D are mostly limited with insufficient presentation and lack of interaction. However, applying 3D techniques surely yield realistic navigation fields. At first glance, it may seem like dealing with 3D map in mobile devices for navigation only present a single particular context (that is user’s location). This initial perception fails to take into account other context like visualization, navigation and interactive technological capabilities. Thus, previous attempts at implementing realistic solutions to the visualization of complex 3D scene in mobile devices’ interactivity of more than two user’s navigation within a scene at the same time were faced with so many obstacles, which unfortunately were left unsolved, despite the enormous ongoing research. This paper aimed at providing solutions to the functional mobile 3D visual navigation system, in particular, one in which mobile devices’ users will navigate within an environment and interact among themselves while tracking their position in real-time. The solutions will be provided through implementing an efficient, scalable dynamic entity navigation solution by means of Bi-A* path finding algorithm. As a result, a 3D model of a real place in a mobile device will be produced, for user’s navigation which will makes it easier to perceive proportions, distances, and recognize landmarks, at the same time interacting with other users.